Synthesis, characterization, processability, mechanical properties, flame retardant, and oil resistance of chlorinated acrylonitrile butadiene rubber. (2nd May 2018) - Nihmath, A.; Ramesan, M. T.
Abstract : Novel chlorinated acrylonitrile butadiene rubber (Cl‐NBR) was prepared from NBR by the alkaline hydrolysis of chloroform by using phase‐transfer catalysis. The formation of Cl‐NBR was monitored by 1 H‐NMR, UV‐Vis, and Fourier transform infrared spectroscopic techniques. The percentage of chlorine attached to the rubber chain was estimated by Volhard method. The effect of polar groups on the structural and thermal properties of Cl‐NBR was analyzed by scanning electron microscopy, X‐ray diffraction analysis, differential scanning calorimetry, and thermogravimetric analysis studies. The flame retardant, oil resistance, cure behavior, and mechanical properties of chlorinated elastomer were also analyzed. The proton NMR revealed the attachment of chlorine in the backbone of NBR with new chemical shift values. The C‐Cl stretching of chlorinated NBR was confirmed from Fourier transform infrared. The UV spectrum also supported the formation of chlorinated unit in the NBR chain through the shifts and broadening of absorption peaks. The X‐ray diffraction analysis pattern indicated a decrease in the amorphous domain of NBR with an increase in the level of chemical modification. The increased glass transition temperature obtained from differential scanning calorimetry confirms the increased molecular rigidity of the chlorinated NBR and thermal transitions increased with increase in the level of chemical modification. The thermal stability of Cl‐NBR decreased with an increase in chlorine content. The flame and oil resistance of Cl‐NBR was greatly higher than pure NBR due to the increased polarity of modified rubber. The superior tensile strength of Cl‐NBR (4 times higher than pure NBR) and higher oil resistance find applications in pump diaphragms, aircraft hoses, oil‐lined tubing, and gaskets materials with the excellent flame resistant property.